Neglected basicervical neck of femur fracture treated with closed reduction and internal fixation with a cephalomedullary nail alone: A case report (Indian Journal of Case Reports, 2022)
A fractured neck femur presenting beyond three weeks is referred to as a neglected fracture. The current literature is silent about neglected Basicervical fractures. The latter behave more like an intertrochanteric fracture and thus are less prone to complications like non-union and avascular necrosis. We report a case of an adult male of 42 years of age presenting with a 10-month-old history fracture neck of the left femur following high energy injury. We treated the fracture with isolated closed-reduction and internal fixation with PFNA II, as the fracture was basicervical. We have achieved a union in six months of surgery. The patient had an excellent functional status one-year follow-up.